Edukasi Gizi sebagai Bentuk Pencegahan Stunting pada Anak – Anak Siswa TK Kartika Bunda - Risti Kurnia Dewi; Muhammad Agung Satriya (Warta Pengabdian Andalas, 2024)
Stunting, which is a condition that disrupts growth, is currently still a problem in Indonesia, including Padang City. One way to overcome stunting is through nutrition education which aims to increase participants' knowledge in order to achieve behavioural changes towards a more positive direction. In this community service, the location of the activity was carried out at Permata Bunda Kindergarten, Padang with the main target being parents and teachers. The material presented was about stunting and also balanced nutrition eating behaviour, using lecture delivery methods and the distribution of leaflets and posters. The post-test results showed a significant increase (p<0.001) of 3 points in participants' nutritional knowledge. These results indicate that the nutrition education provided can have a positive impact on participants' nutritional knowledge. In the future, it is hoped that nutrition education can be implemented more widely, increasing public awareness of the importance of nutrition, so that the prevalence of stunting in children can be reduced.